Daytime shooting star. 11 - Yamamori, Mika (VIZ Media, LLC, 2020)
"Suzume has moved to Tokyo and is living with her uncle. Mr. Shishio once again declares his love to Suzume, but this time around she can't find it in her heart to trust his words. Instead she chooses to focus on strengthening her relationship with Mamura. But when Mr. Shishio and Mamura face off in a relay race for Sports Day, just who will Suzume root for?"--Page [4] of cover.